Analysis of energy consumption bounds in CMOS current-steering digital-to-analog converters - Chacón, Oscar Morales (2022)
In this paper, an attempt to estimate energy consumption bounds versus signal-to-noise ratio (SNR) and spurious-free dynamic range (SFDR) in CMOS current-steering digital-to-analog converters is presented. A theoretical analysis is derived, including the design corners for noise, speed and linearity for the mixed-signal domain. The study is validated by comparing the theoretical results with published measured data. As result it serves as a design reference to aim for minimum energy consumption. It is found that for an equivalent number of bits (ENOBs), the noise-bound grows at a rate of 22ENOB, whereas the speed-bound increases by 2ENOB−2 and is dependent on device dimensions. Therefore, as the technology scales down, the noise bound will dominate, which is observed for an estimated SNR of about 40 dB in 65 nm CMOS process. The linearity bound is derived from an analysis based on the assumption of limited output impedance, where it is found to be dependent on the device dimensions and increase at a rate of 2ENOB−1. The observations show that it is possible to achieve less energy consumption in all the design corners for different SNR and SFDR specifications within the Nyquist frequency, fs/2.